6 Improving Patient Flow in a Multi-Specialty Assessment Area by Introducing Referral Pathways for Orthopaedics and Plastic Surgery during the COVID-19 Pandemic. (4th May 2021) - Gordon, G; Fadulelmola, A; Scott, S
Abstract: Introduction: The COVID-19 pandemic has seen fundamental organisational changes to emergency departments internationally. Specialties throughout the hospital setting have been asked to change their working practice, often with the aim of adapting to new processes in emergency departments. Early in the pandemic, the orthopaedic team at one district general hospital were required to provide 24/7 onsite cover in a multi-specialty area. Confusion over the referral pathways of two specialties (orthopaedics and plastic surgery) led to increase waiting times, constrained patient flow and poor patient and staff satisfaction. Method: This quality improvement project occurred over three cycles of data collection and intervention over a two-month period. A novel referral pathway was developed and implemented after discussion with consultants in orthopaedics, plastics, and emergency medicine. Interventions included staff teaching, clarifying of roles at morning meetings and the deployment of posters. Results: In cycle 1, 39% of orthopaedic referrals were inappropriately referred. By cycle 3, 0% of orthopaedic patients were inappropriately referred. Average time in department for patients referred to orthopaedics improved from 124 minutes to 88 minutes. Staff reported increased satisfaction, with appreciation for the clarification on referral criteria. Conclusions: This QUIP demonstrates how simple interventions during times of crisis can solve complex organisational issues.